Respuesta :
x² - 3x - 10
x² = x * x
10 can be factored:
1 x 10 ⇒⇒⇒ difference between factors = 9
2 x 5 ⇒⇒⇒ difference between factors = 3 ⇒ (The correct pair)
(x-5)(x+2) = x(x+2) - 5(x+2)
= x² + 2x - 5x - 10
= x² - 3x - 10
∴ x - 5 = 0 ⇒⇒⇒ x = 5
x + 2 = 0 ⇒⇒⇒ x = -2
I have attached algebra tiles for the given equation.
x² = x * x
10 can be factored:
1 x 10 ⇒⇒⇒ difference between factors = 9
2 x 5 ⇒⇒⇒ difference between factors = 3 ⇒ (The correct pair)
(x-5)(x+2) = x(x+2) - 5(x+2)
= x² + 2x - 5x - 10
= x² - 3x - 10
∴ x - 5 = 0 ⇒⇒⇒ x = 5
x + 2 = 0 ⇒⇒⇒ x = -2
I have attached algebra tiles for the given equation.
![Ver imagen Matheng](https://us-static.z-dn.net/files/d67/f376b79627e26725f08fc2ffece7709e.jpg)